Effects of climate change: Equity andsocial justice actions in environmental sustainability - Longar Blanco, María del Pilar; Santana Quintero, Talía; Oliver Espinoza, Rubén; Velázquez García, Lydia; Cedillo Hernández, Antonio (Ingeniería Solidaria, 2025)
Objective: The purpose of this research was to analyze how key concepts in the scientific literature on sustainability, climate change, and resilience are interrelated, in order to obtain both quantitative and qualitative perspectives on emerging trends in these fields of study.Methodology: A qualitative approach was employed through bibliographic network analysis, using VOSviewer to examine the frequency and co-occurrence of terms.Results: Seven clusters were identified, revealing specific subthemes related to adaptation, climate change, governance, resilience, and capabilities.Conclusions: The analysis of bibliographic networks and the identification of emerging terms provide a solid foundation for future studies addressing sustainability in urban and rural contexts affected by climate change.Originality: This study offers an innovative contribution by using VOSviewer to explore the interconnections between key concepts, enabling a clearer understanding of emerging trends in the scientific literature on climate change and sustainability.Limitations: Although the qualitative approach was useful for identifying patterns in bibliographic networks, a more in-depth quantitative analysis of the impact of these concepts on practice was not included, which limits the generalization of the results at a global level.